Scenarios for the employment of people with disabilities by work integration social enterprises in Latvia - Licite - Kurbe, Lasma; Sevcuna, Liva (Serbian Journal of Management, 2023)
Employment is an important part of adult life, yet access to the labour market for people with disabilities is limited. A solution is to promote the development of work integration social enterprises (WISEs), yet this requires more support. Therefore, the research aims to identify factors influencing the employment of persons with disabilities by WISEs and design scenarios for promoting the employment of persons with disabilities in Latvia in the context of social entrepreneurship.The research performed a systematic theoretical review to identify the factors, their scope and characteristics as well as their significance and applied analysis, synthesis and deduction for the identification and classification of the factors. The scenario method was employed to identify employment opportunities for people with disabilities, yet an assessment of the scenarios was performed by applying the Analytic Hierarchy Process (AHP), which involved experts engaged in social entrepreneurship.The research found that the most effective way to promote the employment of people with disabilities by WISEs was to increase the scope of national support instruments, and that the use of municipal support instruments was essential. The national support scenario involved partly subsidising wages for disabled employees employed by WISEs and support for long-term investment in WISEs.
Keywords: work integration social enterprises, social entrepreneurship, people with disabilities